Applicability of iron based coagulants for pre-treatment of coal seam water. Issue 1 (February 2017) - Lin, Jack; Couperthwaite, Sara J.; Millar, Graeme J.
Highlights: Iron coagulants effective for removal of dissolved Si, Ba, Ca and Sr from simulated coal seam water. Salinity of CS water impacts the removal performance of silicate and alkaline earth ions. Variable CS water compositions alter ion removal but not to extent of solution salinity changes. Organic contaminants and particulates in real CS water inhibit coagulant performance. Abstract: This study reports the novel application of iron based coagulants to remove dissolved species from coal seam water. Pre-treatment of coal seam (CS) water from coal seam gas operations is required to minimise fouling of downstream membranes. The behaviour of ferric chloride and ferric sulphate with both simulated and actual coal seam water was studied by jar tests. Dissolved silica was the major species eliminated by either coagulant with >80% removal for simulated coal seam water. Barium ions were highly removed, in contrast to magnesium. Salinity of the CS water sample influenced the coagulant ability to reduce dissolved silica which may be due to differences in floc structure and the cation demand of the solution. Varying the simulated CS water composition revealed that silica removal could be promoted albeit it was not clear this outcome was related to the presence of a particular species in solution. Use of real CS water resulted in inhibition of the silica removal mechanism which was ascribed to the presence of organic materials and turbidity which were not accounted for in simulated solutions. Residual iron levels also seemed to increase when real CS water was tested, and with ferric sulphate the issue of contamination of treated water with sulphate species arose, an issue which may impact downstream membrane fouling. As dissolved silicates and alkaline earth ions are of primary concern relating to scaling of water treatment equipment and membranes, a deeper understanding of coagulant performance is warranted.